RETRACTED ARTICLE: Antidiabetic, renal/hepatic/pancreas/cardiac protective and antioxidant potential of methanol/dichloromethane extract of Albizzia Lebbeck Benth. stem bark (ALEx) on streptozotocin induced diabetic rats - Danish Ahmed; Vikas Kumar; Amita Verma; Pushpraj S Gupta; Hemant Kumar; Vishal Dhingra; Vatsala Mishra; Manju Sharma (BMC Complementary Medicine and Therapies, 2014)
Abstract Background Hypoglycemic and/or anti-hyperglycemic activities have been recorded with numerous plants, many of which are used as traditional herbal treatments of diabetes. Albizzia Lebbeck Benth. stem bark have been used in traditional medicine along with some preliminary reports on its hypoglycemic action. The aim of present investigation was to evaluate the antidiabetic and antioxidant activities of methanolic extract of stem bark of Albizzia Lebbeck Benth. in streptozotocin induced diabetic rats. Methods The powdered stem bark of Albizzia Lebbeck Benth.. was extracted with methanol (MeOH) using soxhlation method and subjected to phytochemical analysis. The methanol/dichloromethane extract of Albizzia Lebbeck Benth. (ALEx) was concentrated to dryness using Rotary Evaporator. Diabetes was experimentally induced in the rats by single intraperitoneal administration of Streptozotocin (60 mg/kg). They glycemic control was measured by the blood glucose, glycated heamoglobin and plasma insulin. The oxidative stress was evaluated in the liver and kidney by level of antioxidant markers and various biochemical parameters were assessed in diabetic control and extract treated rats. Results Streptozotocin induced diabetic rats depicted the increased blood glucose levels, total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-c), diminished level of high density lipoprotein cholesterol (HDL-c) level and perturb level of antioxidant markers. Oral administration of MeAL at a concentration of 100, 200, 300 and 400 mg/kg b.w daily for 30 days results a momentous decrease in fasting blood glucose, glycated heamoglobin and enhancement of plasma insulin level as compared with STZ induced diabetic rats. Furthermore, it significantly (p < 0.05) decreased the level of TC, TG, and LDL-c, VLDL-c. While it increases the level of HDL-c to a significant (p < 0.05) level. The treatment also resulted in a marked increase in reduced glutathione, glutathione Peroxidase, catalase and superoxide dismutase and diminished level of lipid peroxidation in liver and kidney of STZ induced diabetic rats. Histopathological studies suggest the diminution in the pancreatic, liver and cardiac muscle damage. Conclusion Our research exertion clearly indicates the considerable antihyperglycemic, antihyperlipidemic, antioxidant & pancreas/renal/hepatic/cardiac protective action of ALEx.